IMPLIKASI PERAN AYAH DALAM MENDIDIK ANAK DARI KISAH KETAATAN NABI IBRAHIM - Hisan Mursalin; Hilyatun Mufidah (Jurnal El-Audi, 2023)
Obedience in worshiping and carrying out Allah's commands is one of the characteristics that every servant must have towards his Lord. And of course, this noble character must be developed and instilled in every human being from an early age, so that later they will get used to it and become obedient individuals in all orders both in this world and the hereafter. But in actual fact, there are still many parents who fail in educating their children to obey. Allah Himself describes the nature of obedience through the life stories of the Prophets. Among them is the story of the obedience of a father and prophet of Allah Ibrahim 'alaihi salam who was followed by his son prophet Ismail to fulfill the commandments of Allah. The intention of this research is to find out how the description of the obedience of Prophet Ibrahim and the role of a father in fostering his son's obedience. In this study, the author used a qualitative approach with the method of description analysis and maudhu'i interpretation. The author then notes that Prophet Ibrahim had an eternal nature of obedience, fulfilling the commands and tests that Allah gave him without hesitation, and he managed to instill this attitude of obedience in his son Ismail. It is the author's desire that fathers as family educators can make the story of Khalilullah Ibrahim Qudwah Hasanah in building and developing the noble traits that Allah promises in the hereafter.